Psychological Well-Being is Essential to WellBeing: Malaysia Evidence - Pang, Mary; Lai, Ming-Ming; Chong, Lee-Lee (International Journal of Psychosocial Rehabilitation, 2020)
The transition event into retirement can be considered as a trivial life event in old age. Nevertheless, psychological well-being is important because it may benefit an individual to achieve greater wellbeing during retirement. Hence, this paper examines the dimensions of psychological well-being of retirees in Malaysia via thematic analysis using Nvivo software. An in-depth personal interview was conducted on a total of fifty retirees aged 45 and above from seven selected states in west Malaysia. The results of this study were found to be consistent with self-determination theory as well as the six dimensions of psychological well-being developed by Ryff and Keyes in 1995. The thematic analysis managed to identify six themes, namely acceptance of strength and weakness, continuing improvement, meaningful activities/ experience, capacity to reduce stress, selfcontrol, and quality relationship. Given its significance, the results further imply that one has to achieve a certain level of psychological well-being to further enhance one’s overall well-being. Hence, it can be concluded that one has to have both psychological well-being and subjective well-being rather than dealing with each well-being separately. More importantly, both well-being may have an interdependence relationship and complement one another.